Utilisation of optical flow algorithms to monitor development of tail biting outbreaks in pigs - Li, Y; Johnston, L; Dawkins, MS (MDPI, 2020)
A study was conducted to evaluate activity changes in pigs associated with the development of tail-biting outbreaks using optical flow algorithms. Pigs (n = 120; initial body weight = 25 ± 2.9 kg) housed in four pens of 30 pigs were studied for 13 weeks. Outbreaks of tail biting were registered through daily observations. Behavior of pigs in each pen was video-recorded. Three one-hour video segments, representing morning, noon, and afternoon on days 10, 7, and 3 before and during the first outbreak of tail biting were scanned at 5-min intervals to estimate time budget for lying, standing, eating, drinking, pig-directed behavior, and tail biting. The same video segments were analyzed for optical flow. Mean optical flow was higher three days before and during the tail-biting outbreak, compared to 10 days before the outbreak (p < 0.05), suggesting that pigs may increase their activity three days before tail-biting outbreaks. All optical flow measures (mean, variance, skewness, and kurtosis) were correlated (all p < 0.01) with time spent standing, indicating that movement during standing may be associated with optical flow measures. These results suggest that optical flow might be a promising tool for automatically monitoring activity changes to predict tail-biting outbreaks in pigs.